Evaluation of the effectiveness and mechanism of action of the Chang-Kang-Fang formula combined with bifid triple viable capsules on diarrhea-predominant irritable bowel syndrome - Sun, Jing; Zhang, Mengqiu; Liu, Wei; Liu, Youqian; Zhang, Dongjian; Fan, Xinyu; Zhang, Jian; Li, Tian; Lu, Min (Frontiers in Microbiology, 2023)
The Chang-Kang-Fang (CKF) formula, a traditional Chinese herbal formula, can decrease serotonin (5-HT) levels and treat irritable bowel syndrome (IBS). Probiotics have a better synergistic effect on diarrhea-predominant IBS (IBS-D) when combined with 5-HT3 receptor antagonists. The present study aimed to elucidate the efficacy and the mechanisms of action of the CKF formula combined with bifid triple viable capsules (PFK) against IBS-D. The rat models of IBS-D were induced by gavage with senna decoction plus restraint stress. The CKF formula, PFK and their combination were administered to the rats. Their effects were evaluated based on general condition of the rats and the AWR score. The levels of 5-HT and fos protein in the colon and hippocampus were measured by immunohistochemistry. The levels of SP and VIP, as well as ZO-1 and occludin in the colon, were determined by enzyme-linked immunosorbent assay and immunohistochemistry. The intestinal microbiota in faeces was analyzed by 16S rRNA high-throughput sequencing. The results showed that the oral CKF formula combined with PFK (CKF+PFK) could significantly relieve the symptoms of IBS-D, including elevating the weight rate and decreasing the AWR score. Compared with the MC group, administration of CKF+PFK significantly reduced the expression of fos in the colon and hippocampus and that of 5-HT, SP and VIP in the colon and increased the levels of 5-HT in the hippocampus and ZO-1 and occludin in the colon. The above indexes exhibited statistical significance in the CKF+PFK group relative to those in the other groups. Moreover, treatment with CKF+PFK improved the diversity of intestinal microbiota and the abundance of Firmicutes, Lachnospiraceae and Ruminococcaceae but decreased those of Bacteroidetes and Prevotellaceae. The CKF formula combined with PFK may have a synergistic effect on IBS-D by slowing gastrointestinal motility, lowering visceral hypersensitivity, enhancing the intestinal barrier function and modulating the composition of intestinal microbiota.